Nanomodifying of Gypsum Binders with Carbon Nanotubes - Derevianko, Victor; Дерев’янко, Віктор Миколайович; Kondratieva, Natalia; Кондратьєва, Наталія Вікторівна; Hryshko, Hanna; Гришко, Ганна Миколаївна; Moroz, Volodymyr; Мороз, Володимир Юрійович (My University, 2022)
One of the directions in development of nanotechnologies used for production of building materials, development of theoretical and practical methods applied for improved properties of finished products and operational constructions in Ukraine consists in use of nanosystems for regulation of material structure and binder properties. The hydration mechanism of mineral binders in the presence of nanomodifiers is quite poorly described in the scientific literature, but the results of laboratory studies confirm their significant impact on the technological process and changes in physical and mechanical properties. Studies on influence caused by nanomodifiers as well as on the mechanism of gypsum binder hydration in the presence of nanomodifiers are topical. Purpose. Studying the mechanism of hydration process, structure and properties of gypsum binders in the presence of carbon nanomodifiers. Conclusions. Introduction of carbon nanostructures into gypsum compositions affects first of all the rate of chemical reactions (hydration of binders), morphology of crystals and composition structure. Use of a relatively small amount of modifier makes it possible to change the structure of mortar or concrete, significantly increase the strength characteristics and improve the physicochemical properties. Carbon nanotubes are one of modifiers. They are mainly neutral with respect to the components of the binder solution and affect the hydration process by increasing the surface energy, creating crystallization centers and nanoreinforcing the structure. For achieving a more efficient action of the nanomodifier mechanical or chemical destruction of separate chemical bonds on the surface of nanotubes is applied (functionalization). Functionalization of carbon nanotube surface gives an opportunity to disperse them more evenly throughout the volume of the modified material; it also contributes to reduction of sedimentation effect and provides chemical interaction between nanotubes and matrix of the substance. Modification of gypsum with nanomaterials increases its compression strength and bending strength as well as watertightness. It was experimentally established that the optimal concentration of BHT with the greatest increase in strength observed was 0.005% - 0.05% of the binder dry mass. Providing the same content of nanomodifiers in the gypsum matrix (0.035%) the maximum increase of compression strength (28-30%) is achieved by means of using BHTs functonalized with hydroxyl groups. Одним із напрямків розвитку нанотехнологій виробництва будівельних матеріалів, розробки теоретичних та практичних методів покращення властивостей готових виробів та експлуатаційних споруд в Україні є використання наносистем для регулювання структури матеріалів властивостей в’яжучих речовин. Інформації щодо механізму процесів гідратації мінеральних в'яжучих речовин в присутності наномодифікаторів в науковій літературі досить мало, але результати проведених лабораторних досліджень підтверджують їх значний вплив на технологічний процес і зміни фізико-механічних властивостей. Дослідження впливу і механізму процесу гідратації гіпсових в'яжучих в присутності наномодифікаторів є актуальними. Мета статті. Дослідження механізму процесу гідратації, структури і властивостей гіпсових в'яжучих в присутності вуглецевих наномодифікаторів. Висновок. Введення в гіпсові композиції вуглецевих наноструктур впливає в першу чергу на швидкість хімічних реакцій гідратації в’яжучих речовин, морфологію кристалів та структуру композиції. Використання досить незначної кількості модифікатора дає можливість змінити структуру розчину або бетону і значно підвищити міцнісні характеристики та покращити фізико-хімічні властивості. Одним із наномодифікаторів є вуглецеві нанотрубки, які в основному нейтральні по відношенню до складових розчину в’яжучої речовини і впливають на процес гідратації за рахунок збільшення поверхневої енергії, створення центрів кристалізації та наноармування структури. Для більш ефективної дії наномодифікатора проводиться руйнування механічним або хімічним способом (функціоналізація) окремих хімічних зв’язків на поверхні нанотрубок. Функціоналізація поверхні вуглецевих нанотрубок дозволяє більш рівномірно диспергувати їх по всьому об'єму модифікованого матеріалу, сприяє зниженню седиментаційного ефекту і забезпечує хімічну взаємодію між нанотрубками і матрицею речовини. Модифікація гіпсу наносистемами збільшує його міцність на стиск та згин, а також водонепроникність. Експериментально встановлено, що оптимальна концентрація ВНТ становила 0,005% - 0,05% від сухої маси в’яжучого, при якому спостерігалось найбільше збільшення міцності. При однаковому вмісті наномодифікаторів в гіпсовій матриці (0,035%) максимальний приріст міцності при стисненні досягається при використанні ВНТ функціоналізованих гідроксильними групами і становить 28-30%.
Наномодифікація гіпсових в'яжучих вуглецевими нанотрубками
Keywords: nanomodifying; наномодифікування; gypsum binders; гіпсові в'яжучі; carbon nanotubes; вуглецеві нанотрубки; hydration; гідратація; nanosystem; наносистема; затверділа структура; solidified (hardened) structure